The 2018 Rhodes Scholars-elect - Editors (New Zealand Science Review, 2017)
​Prestigious Rhodes Scholarships have been awarded to three outstanding young New Zealanders to carry out postgraduate study at the University of Oxford (UK). The 2018 Rhodes Scholars-elect are: Jean Balchin from the University of Otago, Jamie Beaton from Harvard University, and Marco de Jong from the University of Auckland. Jean Balchin, aged 23, studied at Waihi College, and is completing a Bachelor of Arts Honours in English Literature at the University of Otago. Jean’s passion is science communications. As an intern with the Science Media Centre, the country’s independent source of information for the media on all issues related to science, she wrote A History of NZ Science in 25 objects. In addition, Jean is an accomplished pianist, exhibited artist, a performer and has a green belt in Judo. She is also an active volunteer with the Life Matters Suicide Prevention Trust and contributed to the Break the Silence series on youth suicide run by the New Zealand Herald earlier this year.At Oxford she proposes to study for a Doctor of Philosophy (DPhil) examining Social Darwinism. She says his theory of competition has been perverted to explain and justify status inequalities between different ethnic groups. She proposes a future career in education or academia. Jamie Beaton, aged 22, studied at King’s College in Auckland and graduated from Harvard University in three years with a double degree in Applied Math and Economics as well as a Master of Science in Applied Math. While an undergraduate, Jamie founded Crimson Education, which provides international and domestic university admissions consulting, tutoring and career mentorship and is now the largest personalised education company in the Southern Hemisphere. He recently participated in the United Nations High-level Political Forum on Sustainable Development (HLPF) looking at alleviating poverty. While at Crimson, Jamie has observed the powerful disruptive impact of technology, including digitisation, artificial intelligence, and automation and how it is reshaping industry. This has influenced his decision to pursue a Master of Philosophy/Doctor of Philosophy (MPhil/DPhil) in economics at Oxford, focusing on the impact of automation on labour markets. In particular, he wants to ‘leverage Oxford’s global leadership in the impact of technology on the working world from the Oxford Martin Programme and economics faculty’. Marco de Jong, aged 22, studied at Auckland Grammar, before completing a Bachelor of Arts (Honours) and is currently completing a Master of Arts at the University of Auckland. Marco’s Samoan ancestry has helped him find a passion for the Pacific. He is currently learning gagana Sāmoa. With others, he formed and energised the University’s History Society, of which he is currently President. Through the school’s outreach programme he has visited 50 schools, engaged with low decile schools and encouraged Pacific students to study Pacific history. He is also a Tuākana, mentoring all undergraduate Māori and Pacific history students, which has made a huge difference for dozens of students. At Oxford, Marco proposes to study for a Doctor of Philosophy (DPhil) under New Zealand historian and fellow Rhodes Scholar, James Belich. He proposes to focus on climate change diplomacy and wants to become a force for the Pacific people through either education, academia or diplomacy, to ensure decisions are made with, and not for, islanders.